Dioscoreaceae endémicas del Perú - León, Blanca (2006)
The Dioscoreaceae family consists of vines and herbs. In the Peruvian flora, the family is represented by 77 species in the genus Dioscorea (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004). Here we recognize 21 endemic taxa. We assigned IUCN threat categories to five species. The endemic taxa in this family occupy a wide range of ecological regions between 100 and 4250 m elevation, from the Subtropical Coastal Desert to the Mesic Shrubland and Dry and Humid Puna and Paramo; however, the majority of endemics are found in the Humid Montane Forest region. Six species endemic to Peru have been reported to occur in the country’s protected areas network.